Exploring Australian national identity : heroes, memory and politics - Donoghue, Jed; Tranter, Bruce (Emerald points., 2018)
This book explores the attitudes and values of Australians, analysing how Australian national values are promoted and reflected by heroic figures (both living and dead) who are identified as important and influential. Who are the 'heroes, saints and sages' that exemplify the Australian national character? Who do Australians, as citizens of a settler society, nominate as their contemporary heroes? What is the role of colonial and post-colonial figures regarding contemporary Australian identity? This book reassesses the influence of convicts, bushrangers, Ned Kelly, the ANZACS, sporting heroes, and the nation's most 'important people' in terms of national identity. Sporting 'heroes' such as Don Bradman, and historical figures like Ned Kelly might be expected to feature prominently but the authors identify other nationally important Australians, and gauge how well they symbolize Australian national identity. While collective heroes' such as the Anzacs are acclaimed in popular conceptions of national identity, Australians also identify with particular heroic 'individuals who personify practical aspects of the national character and mythscape', including well known federal politicians, surgeons and scientists.